Diversity and larval habitats of mosquitoes (Diptera: Culicidae) in urban areas in Ha Noi, Vietnam - Duong, Van Cuong; Anh Nguyen, Nguyet Thi; Van Nguyen, Vinh (Academia Journal of Biology, 2023)
Although some mosquito-borne diseases have been thriving in Ha Noi city, Vietnam very few studies on mosquitoes have been conducted. Determining how the species composition and abundance of mosquito vectors depend on environmental resources in different habitats addresses where different types of vector control need to be applied. The present study aims to investigate the characteristics of larval habitats and to provide a composition of mosquitoes (Culicidae) in this city. Surveys of larval and adult mosquitoes were carried out from different habitats in urban areas during rainy seasons from 2018 to 2023. Overall, in almost all water containers that were surveyed (80.9%), immature mosquitoes were present. A total of 4593 mosquitoes including 3,950 larvae and 643 adults were collected from 16 sampling sites. Twelve mosquito species belonging to 6 genera were collected and identified. Aedes albopictus and Culex quinquefasciatus were the most common and abundant species, each accounting for 34% of the total collected larval specimens. Five species, Anopheles umbrosus, Culex cintellus, Armigeres subalbatus, Mansonia annulifera, and Lutzia fuscana were the first records for Ha Noi city. The species composition varied between different habitat types. Peri-domestic habitats were the most common breeding sites for mosquitoes in the study area. Noteworthy, species belonging to genus Aedes were abundant in domestic habitats created by anthropogenic materials while that of genus Culex was mainly thriving in large water bodies in both peri-domestic and natural habitats. The current results show a variation in the distribution and abundance of mosquitoes in urban areas of Ha Noi which should be considered for effective planning and implementing mosquito control programs in the city.